Circulating tumor cells in precision medicine: challenges and opportunities. (May 2022) - Rupp, Brittany; Ball, Harrison; Wuchu, Fulei; Nagrath, Deepak; Nagrath, Sunitha
Abstract : The mutational and phenotypic landscape of tumors is dynamic, requiring constant monitoring of cancer patients to provide the most up-to-date and effective care. Circulating tumor cells (CTCs) obtained via liquid biopsy can provide tumor DNA, RNA, and protein information that can aid in the diagnosis, prognosis, and treatment of patients. There have been many recent studies and advances in using CTC enumeration, characterization, and expansion to provide personalized cancer treatment, validating the benefit of using CTCs as a biomarker in standard of care procedures. In this paper, we aim to summarize these advances, their limitations, and suggest future areas of study necessary to bring CTC analysis to clinics. Highlights: Clinical trials have demonstrated the potential of using circulating tumor cell (CTCs) to determine patient treatment. Various protein markers have been discovered in CTCs across multiple cancer types that have been correlated to both patient outcome and treatment efficacy. The ability to perform genomic and transcriptomic studies on single CTC has allowed for heterogeneous profiling of CTCs and advances in the ability to predict patient treatment response and drug resistance. Expanded CTCs have been shown to have similar drug response and drug resistance to the patient' s primary tumor supporting the claim that they can be used for patient specific drug testing.